Misreported Trade - Mohammad Farhad; Michael Jetter; Abu Siddique; Andrew Williams (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper introduces a methodology to measure misreported trade in a consistent way across countries and over time. Our methodology does not require any assumptions about which countries may be more or less likely to misreport – rather, all indices are derived endogenously with available trade data. We derive seven specific indices related to overall misreporting, as well as over- and under-reporting of exports and imports. Applying this method to existing bilateral trade data on the HS 4-digit level from 1996-2015, we present several rankings and describe a few prominent cases, such as China. Overall, our indices can explain intuitive developments well and should help researchers to study countries' trade misreporting in a global dimension that is comparable across countries and over time. We conclude the paper with an application, focusing on the role of tariff and VAT rates as predictors of import under-reporting. As predicted by economic theory, case studies, and economic intuition, we find positive correlations for both tariff and VAT rates with import under-reporting. These results are robust to the inclusion of potentially confounding factors, as well as country- and time-fixed effects.
Keywords: F13; F14; H26; 330; international trade; trade misreporting; tariffs rates; VAT rates